Students’ Perceptions of Using Traditional and Digital English Textbooks to Improve Students' Learning Interest - Ahmad Samat; Geminastiti Sakkir; Hasriani G (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2026)
The purpose of this research is to analyze students’ perceptions of using traditional and digital English textbooks in improving learning interest. This study employed a quantitative method with subjects were 29 students of class XII.1 at SMAN 9 Tana Toraja, selected through cluster random sampling. Data was collected through a perception questionnaire. The results showed that students had positive perceptions of both types of textbooks. The use of traditional textbooks obtained a mean score of 44.38 with a standard deviation of 4.896, where 4 students (14%) were categorized as having very high perception and 25 students (86%) as high. Meanwhile, the use of digital textbooks obtained a mean score of 48.17 with a standard deviation of 5.795, with 15 students (52%) categorized as very high and 14 students (48%) as high interest. Therefore, it can be concluded that the use of textbooks, whether traditional or digital, contributes positively to students’ perceptions and learning interest.